ASPEK GENETIK, OBJEKTIF DAN AFEKTIF DALAM PENERJEMAHAN - Donie Fadjar Kurniawan (Institut Seni Indonesia Surakarta, 2006)
Translation have been practiced and developed for approximately well over 5000 years as from the Egyptian Old Kingdom and the Greek philosophy. It is commonly said that translation refers to reproducing the closet natural equivalent message from source language into target language. The evolution of linguistic theories and transaltion studies comes to two important paradigms of translation researchs. First in product oriented translation. Here, the translator should successfully replace the message from source language into target language. Furthermore, the second paradigm is process oriented translation. In process oriented translation, the focus is on the process of producing the equivalent message cognitively, - in iblackbox' translator In order to get a good process translation, the translator at least have to explore the three aspects withn it The three aspect are Genetic (the producer of the translation) , Objective (transaltionas an object) and Affective (the affect of translation into the reader).Keywords : source language(SL), target language(TL), genetic, objective, affective aspects.